Polpas de açaí e juçara: bioacessibilidade de compostos antioxidantes, atividade citotóxica e qualidade nutricional de polpas “in natura” e processadas - Cordeiro, Noélle Khristinne (2024)
Açaí (Euterpe oleracea and E. precatoria) and juçara (E. edulis) are fruits recognized for their high nutritional and energy value. The bioaccessibility of the bioactive compounds present in these fruits, as well as their antiproliferative action, can reveal significant differences between species. Furthermore, the growing demand for açaíbased products has driven its industrialization, which can lead to a reduction in its nutritional and functional value. The objective of this research was to determine the bioaccessibility of antioxidant compounds from açaí and juçara fruit pulps, evaluate their cytotoxic effects against human colon adenocarcinoma cells (Caco-2) and evaluate physicochemical and nutritional characteristics of in natura pulps and products. açaí industries. Three studies were carried out, namely: I) bioaccessibility based on phenolic compounds, anthocyanins and antioxidant activity of the pulps of E. oleracea, E. precatoria and E. edulis, and the cytotoxicity of the pulps against Caco-2 cells; II) proximal and mineral characterization (potassium, calcium and magnesium) and determination of ascorbic acid content, total titratable acidity (TTA), soluble solids (SS) and SS/TTA ratio of the pulps of the three species; and III) comparative analysis of the minerals potassium, calcium and magnesium, SS, dry matter, phenolic compounds, anthocyanins and antioxidant activity between in natura and processed açaí pulps (ice cream). The results showed that the pulps digested in vitro presented greater bioaccessibility of bioactive compounds, especially in the pulp of E. precatoria in relation to the pulps of E. edulis and E. oleracea. Greater cytotoxic effects on Caco2 cells were observed in the bioaccessible pulps of E. edulis and E. precatoria in relation to E. oleracea. In the proximal characterization, the E. edulis pulp showed higher ash, protein and carbohydrate contents. E. oleracea presented the highest lipid contents and E. precatoria, the highest fiber contents. E. edulis also had higher ascorbic acid content and higher total acidity. E. oleracea showed the highest potassium, calcium and magnesium content, and E. precatoria showed the highest soluble solids content and the highest SS/TTA ratio. Higher levels of potassium, calcium, magnesium, phenolic compounds and greater antioxidant activity were found in in natura pulps, while processed pulps had a higher content of soluble solids and dry matter. These results show that the pulp of E. precatoria has the highest bioactive potential among the species studied, and that its antiproliferative effect against Caco2 cells was similar to the fruits of E. edulis. The pulp of E. edulis, juçara, presented higher levels for most of the physical-chemical and nutritional variables analyzed, demonstrating its nutritional potential comparable or superior to açaí. The addition of ingredients and food additives to açaí pulp reduces its nutritional and antioxidant composition, as they lead to significant reductions of mineral and bioactive contents.